The Linguistic Representation of Women in Hayao Miyazaki's Movies - Noémi Gajdos (Humán Innovációs Szemle)
In this paper, I will explore the concept of 'yakuwarigo' (役割語 role language) in Japanese language and present text analysis of three female characters, Eboshi, Rin and Yubaba from two anime movies of Hayao Miyazaki (Princess Mononoke, Spirited Away). My aim is to demonstrate how the well-known director employs role language, particularly masculine language, to empower his female characters to take on prominent roles in a society where men traditionally hold dominance. In terms of film analysis, Miyazaki places his female characters in the public sphere, making them active participants in the storyline while consistently defying traditional Japanese feminine conventions. This study is closely tied to the field of gender linguistics and linguistic ideology from an analytical perspective, aiming to illustrate how Miyazaki's female characters diverge from linguistic norms in their dialogues.